Visual transparent & visual occlusion: An EEG and COP study - Goh, K.; Morris, Susan; Lee, W.; Ring, A.; Tan, T. (2016)
Electroencephalography (EEG) and centre of pressure (COP) data were recorded in young adults for 60 seconds during standing in visual transparent (VT) and visual occlusion (VO) conditions. In both of these conditions, participants wore VO liquid crystal spectacles which allowed the experimenter to accurately control visual information being presented or occluded to the participant. Alpha band (8-13 Hz) revealed significant differences in channel-averaged power spectrum in these two conditions, but not theta band (4-8 Hz) and beta band (13-30 Hz). In order to determine which channels contributed to these bands, region-averaged and single-channel power spectrum were computed which revealed similar patterns for eyes-open (VT) and eyes-closed (VO) conditions in each band. COP analysis was performed to understand postural steadiness in VT and VO conditions; the analysis indicated significant and larger time-domain distance measures (mean velocity), time-domain hybrid measures (mean frequency and sway area) and frequency domain measures (centroidal frequency) in the VO condition. The increased of alpha power in most frontal and posterior regions was indicative of the cortical processing of vision.